Correlation of Clinical Examination, Mammography and Color Doppler Ultrasonography with Histopathological Findings in Patients of Carcinoma Breast Undergoing Neo-adjuvant Chemotherapy - H.B., Govardhan; Thimmaiah, Naveen; I, Kaleel; Kashyap, Lalit; Goyal, Surekha; Pradhan, Satyajt; Kumar, Anand; Sherigar, Vishwanath (International Journal of Medical Research and Review, 2016)
Background: This study was conducted to assess the chemotherapeutic response or neoadjuvant chemotherapy by clinical examination, color doppler ultrasonography and mammographic examination and correlate with histopathological findings. Material and Methods: The present prospective clinical study conducted during December 2009 to May 2011 includes 30 patients of breast cancer. All patients received 3-4 cycles of neoadjuvant chemotherapy CAF (Cyclophosphamide 500mg/m2, Doxorubicin 50mg/m2 and 5-FU 500mg/m2). Above patients underwent modified radical mastectomy after 10-15 days from last cycle of chemotherapy. The assessment of the chemotherapeutic response in the breast tumor was done by all three methods with respect to the reduction in the calculated volume. Response of the lymph nodes by reduction in the largest dimension assessed. Results: The correlation between histopathological response with response of the tumor assessed by clinical examination, mammogram and ultrasonography were k=0.219, p=0.017; r=0.570, p=0.009 Vs k=0.077, p=0.628; r=0.449; p=0.047 Vs k=0.538; p=0.000; r=0.714; p=0.001 respectively. The correlation between the chemotherapeutic response assessed by Doppler parameters and histopathological parameters were k=0.339; p=0.04; r=0.075; p=0.77 Vs k=0.440; p=0.765; r=0.297; p=0.207 Vs k=0.44; p=0.767; r=0.114, p=0.633 for RI, PI and Vmax respectively. The correlation between clinical examination, sonography and mammogram with that of histopathologial examination as the gold standard on estimation of the tumor size were t=-0.257, p=0.801; r=0.797, p=0.00 Vs t=2.87, p=0.009; r=0.693, p=0.00 Vs t=0.718, p=0.04; r=0.911; p=0.00 respectively. Conclusion: Mammogram is the best non invasive modality in both assessing the chemotherapeutic response and estimation of size of the residual breast tumor than Clinical examination and Color Doppler Ultrasonography while considering histopathological examination as gold standard. For auxiliary lymph nodes, CE is better than Doppler.